Políticas de cobranza y su incidencia en la situación financiera de la empresa Distribuidora Carranza Hnos S.A.C. 2017 - Meregildo Guevara, Zuly Marilin (2019)
The purpose of this research is to decide the incidence of collection policies in the Financial Situation of the Distribuidora Carranza Hnos, 2017 since there are entities that do not worry about setting and following up on their collection policies reflected in the financial health of the same. This research is descriptive and not experimental because I did not manipulate the variables. The investigation has as a population the Distribuidora Carranza Hnos SAC. For the development of this research, I applied surveys using a questionnaire guide, and analyzed the economicfinancial information through indicators such as financial ratios. I conclude that the implementation of collection policies in the company helped it to increase its liquidity, reduce its collection recovery period, its doubtful collection expenses and that it may have payment capacity to face its obligations with third parties proving that the policies of collections do have a positive impact on the financial situation. It is recommended to perform a better follow-up of the account portfolio that the company has by applying effective procedures, which purpose is to propose new collection policies for the company to implement them and in this way to improve their situation.